Improving the Health Status of Children. Hearing on Examining Proposals To Improve the Health Status of Children, Including S. 435 and S. 525, Focusing on Pediatric Care, Public Health, Mental Health, and Substance Abuse Issues. Committee on Labor and Human Resources. United States Senate, One Hundred Fifth Congress, First Session - Congress of the U.S., Washington, DC. Senate Committee on Labor and Human Resources; Congress of the U.S., Washington, DC. Senate Committee on Labor and Human Resources ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
These hearings transcripts present testimony before the Senate Committee on Labor and Human Resources to address the question of how to improve the health care status of American children. The hearings addressed a range of issues relating to children's health from witnesses with expertise in pediatric care, public health, mental health, and substance abuse. Each witness addressed the following four questions: (1) "What are the health-related needs of children that we should work to fulfill?"; (2) "How can we better address children's health needs through improvements to federally-funded public health programs?"; (3) "How do you propose we address the problem of ensuring health coverage to children who are currently uninsured, and what should be the Federal role in that endeavor?"; and (4) "How might we encourage the private sector to participate in partnerships with our Government and community organizations to address the needs of children?" Specific child health issues addressed by a variety of witnesses included pediatric illness, children not covered by health insurance, quality care, substance abuse, care delivery systems, child and adolescent psychiatric services, oral health, and prenatal care. Speakers included Senators Orrin G. Hatch (Utah), Edward M. Kennedy (Massachusetts) and Barbara A. Mikulski (Maryland); Secretary of Health and Human Services Donna Shalala; hospital administrators and other administrators of organizations concerned with child health. (Author/SD)
Availability: U.S. Government Printing Office, Superintendent of Documents, Congressional Sales Office, Washington, DC 20402.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Child Advocacy; Child Health; Child Welfare; Childhood Needs; Children; Dental Health; Diseases; Health Insurance; Health Needs; Health Programs; Health Promotion; Health Services; Hearings; Mental Health; Pediatrics; Physical Health; Prenatal Care; Preventive Medicine; Substance Abuse; Congress 105th; Legal/Legislative/Regulatory Materials